Enfermedades del frijol - Schwartz, H; Castaño, M.; Rivero C, R. (International Center for Tropical Agriculture, 1979)
Diseases are one of the limiting factors to bean production in L.A. The prevalency and severity of the disease depends on the quantity of inoculum existing in the region, environmental conditions and the quality of the seed used. Data are given on geographic distribution, favorable climatic conditions for development, symptomatology, vectors, type of damage caused and control measures, including var. resistant to (1) fungal diseases, the most numerous and causing the most damage: rust, anthracnose, angular leaf spot, root rot, web blight, gray spot, powdery mildew; (2) virus diseases, some of economic importance transmitted by aphids (BCMV, BYMV); transmitted by whiteflies (BGMV, bean chlorotic mottle, euphorbia mosaic); transmitted by chrysomelids (BRMV, pod mottle, BSMV, yellow mottle); (3) bacterial diseases are few but can be a serious limitation to the crop: common and fuscous blights, halo blight; and (4) nematodes: Meloidogyne sp., Trichodorus spp., Pratylenchus spp., Heterodera spp. (CIAT)